Penerapan Pendekatan Teaching at the Right Level (TaRL) untuk Meningkatkan Hasil Belajar Matematika Peserta Didik di SMA Negeri 3 Medan - Rahma P, Fatma Liana; Siregar, Wildawani; Aisyah, Siti (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2024)
The Teaching at the Right Level (TaRL) approach is a learning approach that is relevant to the Independent Curriculum which was recently launched by the government. This research aims to see how students' learning outcomes have improved after implementing the Teaching at the Right Level (TaRL) approach. This research was carried out at SMA Negeri 3 Medan in the odd semester of the 2024/2025 academic year. The subjects in this research were 36 students in class XI 3-1. This type of research is classroom Action Research (PTK). Data collection techniques use observation and test techniques. The instruments used in this research were observation sheets, diagnostic assessment tests, and, student learning outcomes tests. The research results showed a significant increase from cycle I to cycle II in student completion percentage, average score, and number of students who reached the Minimum Completeness Criteria (KKM). During the pre-cycle, the student's completion percentage was 30.55%, with an average class score of 62.72. In cycle I, the percentage of student completion was 66.66%, with an average score of 72.05. Meanwhile, in cycle II, the percentage of student completion increased to 83.33% with an average value of 85.27. In this way, the Teaching at the Right Level (TaRL) approach can improve students' mathematics learning outcomes effectively.